The Effect of Inpatient Service Image on Community Needs at Abdoel Wahab Sjahranie Hospital - Ulia Fitri; Suwanto Suwanto; Muhammad Rafli Aidillah (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
The hospital is an organization that strives to build its image through quality and safe health services, paying attention to the needs of patients and families, and increasing customer satisfaction. This study aims to see the Effect of Inpatient Service Image on Community Needs at Abdoel Wahab Sjahranie Hospital. This research uses a quantitative type of research with a cross sectional study approach. The population of this study was all pasein who were in the Tulip inpatient room at Abdoel Wahab Sjahranie Hospital with 38 patients so that the study sample used a sampling technique, namely total sampling. There is a relationship between the image of the hospital through service facilities, health workers, and environmental conditions with the needs of the community at Abdoel Wahab Sjahrani Hospital. Recommendations for hospitals to continue tren positive organizational culture that prioritizes service quality, and suggest identifying patient satisfaction with each service in order to evaluate services in the hospital.